Phytochemical Screening and Blood Glucose Response of Red Dragon Fruit Extract in Alloxan-Induced Mice - I Gusti Agung Istri Mas Dianti Pratiwi; Ni Putu Ayu Dian Maharani; Ni Made Asthi Pramesti Kirana; Putu Nadya Asti Utari; I Gede Ngurah Bagus Arthayasa; Luh Gde Evayanti; Made Dharmesti Wijaya (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels, which can lead to various complications. Natural products, including red dragon fruit (Hylocereus polyrhizus), have gained attention for their potential antidiabetic properties due to their phytochemical content, particularly flavonoids. This study aimed to evaluate the phytochemical composition of red dragon fruit extract and its effect on blood glucose levels in alloxan-induced diabetic mice. Phytochemical screening was conducted qualitatively to identify the presence of secondary metabolites. Male mice were divided into five groups: a negative control group (no treatment), a positive control group (metformin 10 mg/kg BW), and three treatment groups (T1, T2, T3) receiving red dragon fruit extract at doses of 18.2, 36.4, and 72.8 mg/kg BW, respectively. Diabetes was induced by a single intraperitoneal injection of alloxan monohydrate (140 mg/kg BW). Treatments were administered orally once daily for 6 days. Blood glucose levels were measured on days 0, 2, 4, and 6. Data were analyzed using the Friedmann test. Phytochemical screening confirmed the presence of flavonoids, tannins, alkaloids, and saponins in the extract. Statistical analysis showed no significant reduction in blood glucose levels after administration of red dragon fruit extract at any of the tested doses (p>0.05). Red dragon fruit extract did not exhibit a significant antihyperglycemic effect in alloxan-induced diabetic mice under the tested conditions. This may be attributed to suboptimal dosage, insufficient flavonoid concentration, or a less effective mechanism of action compared to standard therapy. Further studies are needed to optimize the formulation and evaluate its potential using different extraction methods or in combination with other bioactive compounds.